Legibility considerations for nutrition facts labels: The role of typography in accessing information by aged people with low vision - Hammerschmidt, Christopher; Spinillo, Carla Galvão (InfoDesign, 2021)
This article aims to identify legibility guidelines for aged and low vision people, in order to analyze how information design is applied in formatting rules for nutrition facts labels, according to the Brazilian legislation. Taking into account the national public health scenario, with growing numbers of obesity and overweight, food labeling may perform an important role in guiding healthier nutritional choices. It is relevant to look at the aged population, since trends estimate its growth during the next decades. Given that ageing is often related to visual deterioration, we have selected guidelines for aged readers as well as for low vision readers. The comparative analysis of such guidelines with topics addressed by the Brazilian legislation on the format of nutrition facts labels presented compliance for some points and deviations for other elements. Overall, we have noticed that the legal texts include information design aspects. We also advocate for the relevance of research on the legibility of nutrition facts labels as a means to improve access to information by aged and low vision people.